PRELIMINARY GEOTHERMAL INVESTIGATION IN THE BASIN OF KATERINI (NORTHERN GREECE) - Papachristou, M.; Arvanitis, A.; Kolios, N. (Bulletin of the Geological Society of Greece, 2016)
This paper describes the results of the preliminary surface geothermal exploration conducted by IGME in the basin of Katerini (Northern Greece). It mainly regards temperature measurements at the wellhead of 73 wells and in the interior of five boreholes, as well as sampling and chemical analyses from 18 selected sites. Based on the collected data, three sub-regions of geothermal interest can be distinguished, the most important of which is the area of Kato Agios Ioannis (to the south of the basin), with temperatures around 27oC at the depth of 340m. Nonetheless, the detailed geothermal investigation of this basin requires further systematic research as well as the drilling of at least one deep geothermal exploration borehole.